Prevalence of Tuberculosis in Children - Abdulsattar M.Al-Mashhadani, Mohammed; Al-Majamie, Imad M. E.; Abdulsattar M.Al Mashhadani, Abdulqader; Alezzi, Jalil; Mohamed Aydaroos Aljefri , Hasan (Diyala Journal of Medicine, 2024)
Background: Pulmonary TB is a relatively common disease in developing countries including Iraq . A relatively small proportion (5–10%) of the approximately 2 billion people infected with M. tuberculosis worldwide will develop TB. Objective: To show the prevalence of T.B. among children in Abu-Ghraib city Patients and Methods: A descriptive retrospective center-based study in the Abu-Ghraib health sector (chest and respiratory disease unit) was conducted to show the distribution of TB in children ≤ 18 years from the 1st January 2001 till the 31st December 2020. Results: A total sample of 248 patients which represents 15.1% of all patients with TB in Abu-Ghraib (1642) from1st January 2001 till 31st December 2020. Female (152; 61.2%) and male (96; 38.8%). Most common age group affected was 13-18 years which represents 71.7% of patient. The prevalence of TB in Abu-Ghraib during the study period for children was (3.4/100,000). Conclusion: The prevalence of all forms of TB in Abu-Ghraib during the study period was (3.4/100000). Females were affected more than males with a mean of 6.7+/-1.5 Extra-pulmonary TB was found to be more common than pulmonary TB.